The prospects for the SARS‐CoV‐2 pandemic in Africa - Virginia Quaresima; Matteo M Naldini; Daniela M Cirillo (EMBO Molecular Medicine)
Abstract On December 31, 2019, the Chinese government officially announced the identification of a new type of coronavirus (SARS‐CoV‐2) as the etiological cause of a severe acute respiratory syndrome in Wuhan city, Hubei Province. Over the next weeks, SARS‐CoV‐2 caused a global pandemic as officially declared by the WHO on March 11, 2020, with confirmed cases and deaths in more than 166 countries. We are experiencing a worldwide phenomenon of unprecedented social and economic consequences. Since the beginning of the COVID‐19 outbreak, there have been fears that the epidemic could strongly impact weaker healthcare systems in poor‐resource settings, especially in Sub‐Saharan Africa (SSA). The 2 million Chinese nationals that live and work in Africa could potentially contribute to the spread of COVID‐19 on the continent.